Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Problem Based Learning (PBL) Pada Mata Pelajaran PAI di Kelas VII.1 UPTD SMPN 2 Kecamatan Kapur IX - Jekis Wardi; Syawaluddin Syawaluddin; Deslita Deslita; Refni Wasnani; Azharul Fuaddi; Ikrar Dinata (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low learning outcomes of fourth-grade students at kelas VII.1 UPTD SMPN 2 Kecamatan Kapur IX. The aim of this study is to improve the learning outcomes of fourth-grade students at kelas VII.1 UPTD SMPN 2 Kecamatan Kapur IX through the Cooperative Learning method. The type of research used is Classroom Action Research (CAR) with a Problem-Based Learning (PBL) model. The methods employed in the research consist of two cycles, specifically the Cooperative Learning method. Each cycle consists of four stages: planning, implementation/action, observation, and reflection. Each cycle includes one meeting (3 class hours). The population involved in the study is 12 students. The data collection techniques used are observation, tests, and interviews. The results of this study indicate an improvement in student learning outcomes from the pre-action phase to cycles I and II. The learning outcomes of students in the pre-action phase were 42%, in cycle I (first) increased to 67%, and in cycle II (second) further increased to 92%. Thus, it can be recommended that the implementation of the Cooperative Learning method can enhance student learning outcomes in the material of reading the Qur'an for the 2024/2025 academic year.